Les Missionnaires Belges en Afrique Centrale, Fin 19e-20e Siecle. : L’Evangélisation: pas un monde à part - Blondeel, William (Afrika Focus, 1986)
This contribution is an attempt to define in rather general terms the field in which Belgian catholic missionaries were active in Central Africa at the end of the 19th and in the 20th century. It is not an acceptable synthesis, but rather a "tour d'horizon". The image of the missionary is examined as a consistent whole as well as in its different aspects, such as teacher, medical agent, social worker and researcher. The relation between the mission on the one hand and the whole community life on the other appears as a central issue. KEYWORDS : Belgian catholic missions, (Belgian) Congo, Ruanda- Urundi.